Rationale and design of a prospective, observational, multicentre study on the safety and efficacy of apixaban for the prevention of thromboembolism in adults with congenital heart disease and atrial arrhythmias: the PROTECT-AR study. Issue 9 (22nd September 2020) - Kartas, Anastasios; Doundoulakis, Ioannis; Ntiloudi, Despoina; Koutsakis, Athanasios; Kosmidis, Diamantis; Rampidis, Georgios; Apostolopoulou, Sotiria; Frogoudaki, Alexandra; Tzifa, Afrodite; Avramidis, Dimosthenis; Ntzoyvara, Olga; Liori, Sotiria; et al.
Abstract : Introduction: The risk for stroke in adults with congenital heart disease (ACHD) is increased, especially in the setting of commonly ensuing atrial arrhythmias (AA), namely atrial fibrillation, atrial flutter or intra-atrial re-entrant tachycardia. Data are limited regarding treatment with non-vitamin K oral anticoagulants in long-term studies involving patients with ACHD and AA. Methods and analysis: PReventiOn of ThromboEmbolism in Adults with Congenital HearΤ disease and Atrial aRrhythmias is a prospective, multicenter, single-arm, non-interventional cohort study designed to investigate the safety and efficacy of apixaban for the prevention of thromboembolism in ACHD with AA in a 'real-world' setting. Eligible patients will be evaluated by the means of available registries and clinical counter. The study aims to accumulate approximately 500 patient-years of exposure to apixaban as part of routine care. Enrolment will take place at four ACHD centres in Greece. The first patient was enrolled in July 2019. The primary efficacy endpoint is a composite of stroke, systemic or pulmonary embolism and intracardiac thrombosis. The primary safety endpoint is major bleeding, according to the International Society on Thrombosis and Haemostasis bleeding criteria. Ethics and dissemination: The study protocol has been approved by the institutional review board/independent ethics committee at each site prior to study commencement. All patients will provide written informed consent. Results will be disseminated at scientific meetings and published in peer-reviewed journals. Trial registration number: NCT03854149 ; Pre-results.